Development of a Science Literacy–Based Teaching Module on Biodiversity for Grade X Students at MAS Darul Ihsan Aceh Besar - Dina Ariani; Jalaluddin; Musriadi; Muhammad Ridhwan; Cut Morina Zubainur; Mohd Isha Awang (Postgraduate, University of Mataram, 2025)
The low level of scientific literacy among Indonesian students, as reflected in the results of the Programme for International Student Assessment (PISA), highlights the need for innovative learning strategies that connect biological concepts with real-life phenomena. One alternative is the development of a science literacy–based teaching module. This study aims to develop a teaching module on biodiversity for Grade X students at MAS Darul Ihsan Aceh Besar and to evaluate its feasibility in terms of validity, readability, and practicality. The research employed a Research and Development (R&D) approach using the 4D model. The defining stage was carried out through observation and interviews to analyze learning needs. The design stage produced a draft module, which was then validated by subject matter experts, language experts, and media experts. The revised product was subsequently tested on a limited scale with students and teachers. The results showed that the module obtained an average score of 89% for content, 87% for language, and 90% for presentation and graphics, all categorized as “highly feasible.” The student readability test yielded an average score of 86% (highly feasible), while the teacher practicality test achieved an average score of 88% (highly practical). These findings indicate that the developed module is theoretically valid, practically applicable, and supports contextual learning aligned with the Merdeka Curriculum. In conclusion, the science literacy–based teaching module on biodiversity is considered feasible as an alternative learning resource that can enhance students’ scientific literacy skills, critical thinking, and ecological awareness.